Some Reliability Issues of the Corrugated I-Beam Girder - SOKOŁOWSKI, Damian; KAMIŃSKI, Marcin Marek (Engineering Transactions, 2015)
The main aim of this paper is reliability analysis of the corrugated-web I-girder carried out to verify its susceptibility to the random corrosion of the web and to make a comparison of the results of the first and of the second order reliability analysis. The methodology implemented in the study is based on the stochastic finite element method related to the generalized stochastic perturbation technique, where a discretization of the entire structure is carried out with four-node quadrilateral shell finite elements. This is numerically implemented using the FEM engineering system ROBOT and computer algebra system MAPLE, where all probabilistic procedures are programmed. The perturbation-based results are compared with these coming from the Monte-Carlo simulation and with an analytical solution obtained via symbolic integration carried out in MAPLE also. The indices of reliability are determined for the maximum deflections of the beam as the function of an input coefficient of variation of the web’s thickness whose meaning is the extent of a corrosion process.